Comparative analysis of the automatic fixture design systems - Rodić, Milorad (Journal of Production Engineering, 1993)
This paper provides an analysis of characteristic systems for automatic fixture design. The analysis leads to the conclusion that all such systems can be categorized as either systems for selecting existing fixtures or systems for synthesizing new fixtures. As a result of this research, an integrated approach to fixture design is proposed. The initial phase involves the selection of existing fixtures, which may vary in terms of their operational readiness. The subsequent phase encompasses the design of new fixtures or the incorporation of adjustments and modifications to existing fixtures to accommodate new machining operations.